Wealth and education-related inequalities in the utilisation of reproductive, maternal, newborn, and child health interventions within scheduled tribes in India: an analysis of Odisha and Jharkhand - Rekha S.; Varshini Neethi Mohan; Girija Vaidyanathan; Umakant Dash; V. R. Muraleedharan (BMC, 2024)
Abstract Background The utilisation of Reproductive, Maternal, Newborn and Child Health (RMNCH) services remains lower among the Scheduled Tribes (ST) in India than among the rest of the country's population. The tribal population's poorest and least-educated households are further denied access to RMNCH care due to the intersection of their social status, wealth, and education levels. The study analyses the wealth- and education-related inequalities in the utilisation of RMNCH services within the ST population in Odisha and Jharkhand. Methodology We have constructed two summary measures, namely, the Co-coverage indicator and a modified Composite Coverage Index (CC), to determine wealth- and education-related inequalities in the utilisation of RMNCH indicators within the ST population in Odisha and Jharkhand. The absolute and relative inequalities with respect to wealth and education within the ST population are estimated by employing the Slope Index of Inequality (SII) and the Relative Index of Inequality (RII). Results The results of the study highlight that access to RMNCH services is easier for women who are better educated and belong to wealthier households. The SII and RII values in the co-coverage indicator and modified CCI exhibit an increase in wealth-related inequalities in Odisha between NFHS-4 (2015-16) and NFHS-5 (2019-21) whereas in Jharkhand, the wealth- and education-related absolute and relative inequalities present a reduction between 2016 and 2021. Among the indicators, utilisation of vaccination was high, while the uptake of Antenatal Care Centre Visits and Vitamin A supplementation should be improved. Interpretation The study results underscore the urgent need of targeted policies and interventions to address the inequalities in accessing RMNCH services among ST communities. A multi-dimensional approach that considers the socioeconomic, cultural and geographical factors affecting healthcare should be adopted while formulating health policies to reduce inequalities in access to healthcare.